The immunomodulatory role of matrix metalloproteinases in colitis-associated cancer - He, Luying; Kang, Qianming; Chan, Ka Iong; Zhang, Yang; Zhong, Zhangfeng; Tan, Wen (Frontiers in Immunology, 2023)
Matrix metalloproteinases (MMPs) are an important class of enzymes in the body that function through the extracellular matrix (ECM). They are involved in diverse pathophysiological processes, such as tumor invasion and metastasis, cardiovascular diseases, arthritis, periodontal disease, osteogenesis imperfecta, and diseases of the central nervous system. MMPs participate in the occurrence and development of numerous cancers and are closely related to immunity. In the present study, we review the immunomodulatory role of MMPs in colitis-associated cancer (CAC) and discuss relevant clinical applications. We analyze more than 300 pharmacological studies retrieved from PubMed and the Web of Science, related to MMPs, cancer, colitis, CAC, and immunomodulation. Key MMPs that interfere with pathological processes in CAC such as MMP-2, MMP-3, MMP-7, MMP-9, MMP-10, MMP-12, and MMP-13, as well as their corresponding mechanisms are elaborated. MMPs are involved in cell proliferation, cell differentiation, angiogenesis, ECM remodeling, and the inflammatory response in CAC. They also affect the immune system by modulating differentiation and immune activity of immune cells, recruitment of macrophages, and recruitment of neutrophils. Herein we describe the immunomodulatory role of MMPs in CAC to facilitate treatment of this special type of colon cancer, which is preceded by detectable inflammatory bowel disease in clinical populations.